Finite element simulation of polymethyl-acrylamid foam-filled aluminum 2024-t4 tube under dynamic axial loading / Akbar Othman and Mohd Fahrul Hasan - Othman, Akbar; Hasan, Mohd Fahrul (2012)
This paper presents the numerical studies of two different tubes under axial impact loading structures. The cylindrical tubes are filled with closed-cell polymeric foam. The deformation and failure mechanisms of this material were observed and analyzed numerically using the finite element method. The varied wall thickness and dynamic velocity of impact were examined throughout this paper. In comparison with double cell foamfilled tubes in terms of dynamic loading, mean load and absorbed energy were enhanced, and the weight efficiency of energy absorption is higher. Parameters affecting the performance of the foam-filled tube structures are also studied. The used of polymeric foam as a filler material is superior compared to empty tube thin-walled profile when polymeric foam filled into tubular structure. Finite element software package of ABAQUS version 6.10 was used to analyze the performance of absorbed energy as well as dynamic and mean load characteristics. The polymethyl-acrylamid foam was selected as a filler material and thin-walled metallic material of aluminum 2024-T4 alloy.